2009
DOI: 10.1080/16070658.2009.11734215
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing high socio-economic class mothers’ decision regarding formula-feeding practices in the Cape Metropole

Abstract: * Regarding the level of education, Grade 12 is equivalent to 12 years of schooling;Grade 7 is equivalent to 7 years of schooling.The main aim of the study was therefore to identify the factors that influence high socio-economic class mothers' decisions regarding infant-feeding practices. The objectives were to identify the reasons why high socio-economic class women in the Cape Metropole decide not to breast-feed; to evaluate whether the type and volume of infant AbstractThe aims of the study were to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(19 reference statements)
3
5
1
Order By: Relevance
“…13 Three quarters of the participants in the present study were influenced by advice from others, and these findings concur with those reported by Yee and Chin, and Andrew and Harvey, namely that women reported that their infant feeding choices were influenced by the perceived norm among family and friends.…”
Section: Social Factors (Culture Reference Groups and Social Class)supporting
confidence: 81%
See 3 more Smart Citations
“…13 Three quarters of the participants in the present study were influenced by advice from others, and these findings concur with those reported by Yee and Chin, and Andrew and Harvey, namely that women reported that their infant feeding choices were influenced by the perceived norm among family and friends.…”
Section: Social Factors (Culture Reference Groups and Social Class)supporting
confidence: 81%
“…Implementation of the MBFI in South African mother and child health services, as per the recommendation of the World Health Organization (WHO) and United Nations Children's Fund, is the most likely explanation why the use of infant formula in hospital influenced only 10% of the participants during this period. This is different to the findings of a study performed in Ireland by Martyn,13 in which most of the women were influenced by a milk brand that they had seen in a hospital postnatal ward, making the hospital an advertising arena for infant formula. Yee and Chin also reported different results, indicating that promotional clauses had the highest impact on East Malaysian parents' decision to purchase a particular brand.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Breast physiology was not regarded as a factor that prevented breastfeeding. 60 In the context of HIV, there are even more barriers to breastfeeding. In a study in Uganda 46 , breastfeeding had been stopped at the time of the interview by half of the HIV-positive mothers with infants under two years of age.…”
Section: Child Healthmentioning
confidence: 99%